IoT-based greenhouse technologies for enhanced crop production: a comprehensive study of monitoring, control, and communication techniques - Nagendra Singh; Akhilesh Kumar Sharma; Indranil Sarkar; Srikanth Prabhu; Krishnaraj Chadaga (Systems Science & Control Engineering)
According to various studies, different countries have different climate conditions that affect the quantity and quality of crop production. Farmers want to use novel technologies that can help them produce crops in large quantities with good quality. The greenhouse is one of the rapidly growing technologies used for the production of crops. It protects the crops from changes in external weather conditions and, hence, helps to produce good-quality crops throughout the year. This work proposes a deep study of the technologies used in the greenhouse for the monitoring and control of various environmental parameters that affect the quality and production of the crops. This work also analyses the different communication techniques, relays, and sensors used for monitoring and controlling the different greenhouse parameters. Also, give details on sensors and the advantages and disadvantages of different communication technologies so that farmers can easily understand which technology is most suitable for their greenhouse. This study helps the farmers adopt the best-suited techniques in their green houses that are cost-friendly, easy to use, and have a longer life.